2017
DOI: 10.1038/s41598-017-03134-9
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Occult Blood Test Results of the National Colorectal Cancer Screening Program in South Korea (2006–2013)

Abstract: There has been controversy regarding the clinical utility of fecal occult blood test (FOBT) as a screening tool for colorectal cancer (CRC) in the general population. The purpose of this study was to examine the results of Korea national CRC screening using FOBT from 2006 to 2013 and to evaluate the implementation of the program. We analyzed the results of FOBT, colonoscopy, and the side effects during colonoscopy for the subjects (n = 20,609,909) from the Korea National Health Insurance Cancer Screening datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…This finding is consistent with most of the related reports 8, 35-37. Differences in lifestyle and eating habits 38-42, and differences in screening rates are possible explanations 30, 43, but further research is needed to find the reason for this result.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with most of the related reports 8, 35-37. Differences in lifestyle and eating habits 38-42, and differences in screening rates are possible explanations 30, 43, but further research is needed to find the reason for this result.…”
Section: Discussionsupporting
confidence: 90%
“…The main critical aspects for the management of colorectal cancer are the high rate of tumor relapses after surgery and the frequent and invasive diagnostic tests performed during the follow-up. Other issues are related to the high costs and the low compliance rates of colonoscopy [ 21 ] and the low specificity and sensitivity of the screening tests, such as the faecal occult blood test or the detection of CEA and CA 19.9 biomarkers, which often fail to early identify CRC tumor lesions [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colonoscopy adherence in the population with positive preliminary screening results determines the effectiveness of CRC screening and early diagnosis. However, unsatisfactory levels of colonoscopy adherence have been reported in some studies, and even lower adherence has been reported in China . From 2012 to 2013, data from 14 cities in China showed that among high‐risk urban residents with positive results on preliminary screening with questionnaires, only 33.25% underwent colonoscopy .…”
Section: Introductionmentioning
confidence: 99%